Adaptive walking performance is related to the hip joint position sense during active hip flexion rather than during passive hip flexion - Matsui, Taishi; Hirata, Kosuke; Miyamoto, Naokazu; Akagi, Ryota (Frontiers in Sports and Active Living, 2025)
The purpose of this study was to investigate the relationship between hip joint position sense during active or passive hip flexion and adaptive walking performance across obstacles. After screening, 30 young men with the right dominant leg (age, 21 ± 2 years) participated in the experiment. To measure adaptive walking performance on the first day, the participants stepped over an obstacle underfoot with the left leg just high enough to avoid touching the obstacle. The difference between the height of the knee joint at the moment of crossing the obstacle and the height of the obstacle was normalized to the lower limb length and used to evaluate performance. To measure hip joint position sense on the second day, the participants adjusted their left hip joint angle to the target angle (range of joint motion: 80° of hip flexion) by active or passive hip flexion using a dynamometer. Although the absolute error in hip joint position sense during active hip flexion (6.3° ± 4.4°) significantly correlated with that during passive hip flexion (23.2° ± 11.0°) (r = 0.507, P < 0.001), a notable difference was observed between the two (P < 0.001). The normalized knee joint height was significantly correlated with the absolute error of hip joint position sense during active hip flexion (r = 0.477, P < 0.001) but not during passive hip flexion. The results of this study suggest a strong association between hip joint position sense under conditions that closely resemble actual walking behavior and adaptive walking performance, such as crossing over obstacles.